2D materials inks toward smart flexible electronics. (November 2021) - Moses, Oyawale Adetunji; Gao, Libo; Zhao, Haitao; Wang, Zhuo; Lawan Adam, Mukhtar; Sun, Zhehao; Liu, Kaili; Wang, Jiahong; Lu, Yang; Yin, Zongyou; Yu, Xuefeng
Graphical abstract: Abstract: The significant advancement in 2D materials fabrications has ushered a paradigm shift in material chemistry, which in turn has greatly influenced the manufacturing industries, in terms of products offered to the global community. The development of smart flexible electronics is one of such advancements, with remarkable potentials when intelligently understood and applied. This review aims to provide an up-to-date survey of significant flexible electronics manufactured using 2D materials, analyze the additive manufacturing processes involved, anatomize inks formulation processes, properties, and post-treatment necessary for further advancement in smart flexible manufacturing. Finally, some explicit description of various smart applications of 2D materials inks in batteries, micro-supercapacitors, sensors, and other flexible electronics are highlighted, along with enlightening futuristic glimpse into their innovative integration into soft robotics.